Boosting innovation and entrepreneurship in Polish economy - Klemens, Brygida; Derlukiewicz, Niki; Mempel-Śnieżyk, Anna (Pobudzanie innowacji i przedsiębiorczości w polskiej gospodarce, 2017)
The aim of the article is to examine and assess selected aspects contributing to innovativeness of economy and inciatives used by the Polish government to stimulate the development of innovation and entrepreneurship. in the economy. To achieve this goal, the authors analyzed the dynamics of changes in business environment institutions and the actions and programs conducted in Poland at national level. As a result of the research, it can be stated that the activities undertaken in Poland resulted in numerous BEIs institutions and Poland has developed friendly environment for business. The conducted research confirms the increase of employment in R&D in private sector and a constat increase in R&D finacing by private sector.
Biblioteka Regionalisty, 2017, Nr 17, s. 55-66
Keywords: innovation; entrepreneurship; region; business environment institutions; innowacja; przedsiębiorczość; instytucje otoczenia biznesu